Polycystic ovarian syndrome: Assessment of approaches to diagnosis and cardiometabolic monitoring in UK primary care. Issue 1 (22nd December 2017) - Heald, Adrian H.; Livingston, Mark; Holland, David; Robinson, John; Moreno, Gabriela YC.; Donnahey, Gemma; Duff, Christopher J.; Wu, Pensee; Fryer, Anthony A.
Summary: Introduction: Polycystic ovarian syndrome (PCOS) is one of the commonest endocrine disorders affecting women of reproductive age. We examined the specific tests that are done in primary care to lead to the diagnosis of PCOS, and to support the diagnosis once made. Methods: One thousand seven hundred and ninety‐seven women were identified from a pooled GP practice database. The search included all patients defined with PCOS or related terms. Records included demographic information, medical history (diagnoses), blood test results and whether a pelvic ultrasound scan had been performed. Results: The most common age of PCOS diagnosis was 20‐29 years; 67.7% of the women had at least one concomitant Read‐coded diagnosis. Most pelvic ultrasound scans were performed in the month immediately prior to diagnosis. In the 12 months prior to the diagnosis of PCOS being made, 30.5% of women underwent a measurement of their serum total testosterone level while 29.6% had their serum SHBG measured. For serum oestradiol, the corresponding statistics were 28.4%, LH 45.3% and for FSH 45.5% checked before diagnosis. Fasting blood glucose, random glucose and HbA1c were checked in 10.2%, 18.8% and 4.2%, of women before diagnosis, respectively, but in only 7.9%, 6.0% and 3.4% of women in the 24 months after diagnosis. There was a tendency for endocrine testing (oestradiol, LH, FSH, testosterone, SHBG) to peak in the weeks before diagnosis. For plasma glucose, testing was performed more evenly over time as for serum cholesterol. Of all women diagnosed with PCOS, 32.8% were prescribed metformin, 3.7% antihypertensives, 2.2% statins and 63.5% an oestrogen‐containing contraceptive pill or HRT. Conclusion: The underlying pathophysiology of PCOS is still not fully understood. As a result, treatment is often focused on individual symptoms, not the syndrome itself. Robust laboratory led protocols would provide the necessary information to enable an appropriate diagnostic evaluation/cardometabolic monitoring.